ESTUDO DA PATOLOGIA INFECIOSA BACTERIANA NUMA UNIDADE HOSPITALAR DE CONVALESCENÇA, CUIDADOS GERIÁTRICOS E PALIATIVOS - Ângela Figueirinhas; Maria João Marruz; Ana Maria Bernardo; Manuel Caldas de Almeida (Formifarma, LDA., 2013)
The inappropriate use of antimicrobials has a negative impact, in favoring the appearance of drug-resistant strains on patients, in the ecosystem and in the economy. The hospital studied, Hospital do Mar (HM), specializes in providing care during patient recovery and rehabilitation, as well as palliative and geriatric care, to patients originating from general or intensive care hospitals. It is known that drug-resistant strains occur more frequently among bacteria that cause nosocomial infections as opposed to community acquired infections. Furthermore, in hospitals the high occurrence of drug-resistant strains is concurrent with a high use of antimicrobials. In this study the authors performed a retrospective analysis to characterize the infectious pathology present in the Hospital do Mar, test the sensitivity of the microorganisms present to several antimicrobials, and document the antimicrobials prescribed at the time, with the goal of adjusting the therapeutic protocols currently implemented and decreasing the emergence of drug-resistant strains. This study allowed the implementation of clinical protocols, and established criteria for the selection of antibiotherapy prescriptions for the most common infectious pathologies.